Haze : a novel of a far future - Kerr, Katharine (CaezikSF, 2025)
"Once, Dan flew amongst the stars as a decorated Fleet Officer. Now destitute, he sleeps on the streets of Gleam, trading his body for a drug called Haze that dulls the pain of what he's lost with nothing left to his name but a battered knife, a damaged mind, and a past he can't escape. But he is given a rare second chance when former comrades track him down and make an offer that he never expected. Across the galaxy, the invisible lanes of faster-than-light travel-the shunts-are beginning to fail. One has already vanished without warning. If the rest collapse, entire civilizations will be cut off, stranded, and left to die. The Fleet needs someone who can read the hyperspace currents like no one else. Someone like Dan. But bringing him back into the fold won't be easy-and keeping him alive may be even harder. Thrown together with a crew of misfits and old friends carrying wounds of their own, Dan boards a disguised merchant ship on a secret mission to uncover the truth. What they find will challenge everything they believe-about the shunts, about the Fleet, and each other. And through it all, Dan must battle the addiction that nearly destroyed him... and still might."-- Amazon.com